Skill, race, and income inequality in the wage sector in British Tanganyika - Sascha Klocke (African Economic History Network (AEHN), 2022)
In the literature on wages and income inequality in colonial sub-Saharan Africa, two recurrent themes can be observed: high racial inequality between European colonisers and the colonised African population and high skill premiums, a measure of the ratio of skilled to unskilled wages. For colonial Africa, these high skill premiums have usually been relegated to a mere confirmation of the frequent complaints over skilled labour shortages by colonial officials. Elsewhere, however, they have been identified as an important driver of income inequality, an indicator of human capital formation, and a predictor of long-run growth. Consequently, they warrant further investigation also in the colonial context. In this paper, I investigate the levels and trends in income inequality in the wage sector in British Tanganyika from c. 1920-60. It focuses on the role of skill premiums and racial discrimination, and highlights the complex interrelations between skilled labour supply and demand on the one hand as well as skill premiums and racial income differences on the other. I find that income inequality was, overall, high in the colonial wage sector, although it declined somewhat towards the end of the colonial period. While the overall trend in inequality was driven mostly by racial income differences, skill premiums played an important role, too. Moreover, part of the racial income differences did not stem from outright discrimination, but were linked to a persistent shortage of skilled labour and the resulting import of non-African skilled personnel. Underlying both high skill premiums and high racial income differences was the lack of educational provision for Africans by the colonial authorities. This failure to expand educational opportunities for Africans was also the principal barrier to African economic advancement in the wage sector, much more so than formal colour bars.
Keywords: 330; Lohnstruktur; Einkommensverteilung; Ethnische Diskriminierung; Fachkräfte; Kolonialismus; Britisch; Ostafrika